2007
DOI: 10.1117/1.2799538
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation imaging microscopy studies of osteogenesis imperfecta

Abstract: We have used quantitative second harmonic generation (SHG) imaging microscopy to investigate the collagen matrix organization in the oim mouse model for human osteogenesis imperfecta (OI). OI is a heritable disease in which the type I collagen fibrils are either abnormally organized or small, resulting in a clinical presentation of recurrent bone fractures and other pathologies related to collagen-comprised tissues. Exploiting the exquisite sensitivity of SHG to supramolecular assembly, we investigated whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 26 publications
4
77
1
Order By: Relevance
“…Experimentally we observed this trend and measured a ratio of approximately 2.5. (16) This demonstrates that phase matching considerations based on domain size and randomness can be used to make comparisons of the relative emission intensities in different tissues.…”
Section: Oi Vs Wt Domainsmentioning
confidence: 90%
See 1 more Smart Citation
“…Experimentally we observed this trend and measured a ratio of approximately 2.5. (16) This demonstrates that phase matching considerations based on domain size and randomness can be used to make comparisons of the relative emission intensities in different tissues.…”
Section: Oi Vs Wt Domainsmentioning
confidence: 90%
“…This is because many diseases are characterized by defects or changes in the assembly of collagen in the respective tissue and we thus suggest that the SHG imaging modality has great potential as a clinical diagnostic tool. For example, the connective tissue disorder Osteogenesis Imperfecta (OI) is characterized by abnormal collagen assembly and we have shown that SHG can reveal differences in the morphology not possible by other optical methods (16). Additionally, SHG has also shown early promise in imaging cancer since malignant tumors often have abnormal collagen assembly relative to normal tissue (9,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, there remains great potential in using detailed polarization analysis to classify normal and diseased tissues, such as cancer and connective tissue disorders, which often have different fibrillar properties. For example, we showed that the SHG anisotropy [40] and SHG-CD responses [33] in the connective tissue disorder Osteogenesis imperfecta (OI) were different than in normal tissues. We also recently showed that SHG polarization signatures could differentiate different collagen isoforms in self-assembled collagen gels which are models for stromal changes in ovarian cancer (Biophysical Journal, submitted).…”
Section: Applicationsmentioning
confidence: 99%
“…In fact, SHG microscopy highlights morphologic changes in collagen structure, which indicate particular disease states, such as tumour invasiveness, as well as indicators of collagen remodelling in tumour stroma, which is playing a key-role in the tumour development from in-situ to invasive stage. Recently, SHG microscopy has been successfully applied to the study of altered physiological conditions of various kinds of tissues, including muscle [94], bones [95,96], and cartilages [97,98]. SHG can be easily combined with TPEF microscopy to realize a particularly powerful tool for connective tissue imaging.…”
Section: Introductionmentioning
confidence: 99%